2021
DOI: 10.1001/jamaoto.2021.1290
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Clinician-Graded Facial Function and Patient-Reported Quality of Life in Adults With Peripheral Facial Palsy

Abstract: IMPORTANCEUnderstanding how the quality of life of adults (Ն18 years) with peripheral facial palsy can be estimated using clinician measures of facial function and patient-reported variables might aid in counseling patients and in conducting research.OBJECTIVES To analyze associations between clinician-graded facial function and patient-reported quality of life in adults with peripheral facial palsy, compare associations between facial function and the physical and social functions of quality of life, and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…This is in line with previous research showing a weak and often non-significant correlation between facial function and the social aspect of QoL in facial palsy. 7 In a previous study, examining factors influencing quality of life in facial palsy, an explained variance of 3.8% was found for a multivariate model predicting FaCE total scores by age, gender, duration of palsy and aetiology. 8 In a follow-up study, the authors found an explained variance of 18.9% in a linear model predicting FaCE total scores by eFACE facial function scores.…”
Section: Discussionmentioning
confidence: 92%
“…This is in line with previous research showing a weak and often non-significant correlation between facial function and the social aspect of QoL in facial palsy. 7 In a previous study, examining factors influencing quality of life in facial palsy, an explained variance of 3.8% was found for a multivariate model predicting FaCE total scores by age, gender, duration of palsy and aetiology. 8 In a follow-up study, the authors found an explained variance of 18.9% in a linear model predicting FaCE total scores by eFACE facial function scores.…”
Section: Discussionmentioning
confidence: 92%
“…Whilst a moderate correlation was demonstrated between FaCE and Sunnybrook scores (Rho = 0.450, p = 0.014), the correlation between FaCE and eFACE was weaker and not statistically significant (Rho = 0.373, p = 0.056). Finally, in a recent meta‐analysis of 3746 patients analyzing associations between clinician and patient rated measures in adults with FNP, the pooled correlation coefficients between facial function and social function on FaCE were 0.324 (95% CI, 0.128–0.495) to 0.397 (95% CI, 0.242–0.532) 61 . The authors concluded that only a small part of QoL was explained by facial function with use of standard scales.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in a recent metaanalysis of 3746 patients analyzing associations between clinician and patient rated measures in adults with FNP, the pooled correlation coefficients between facial function and social function on FaCE were 0.324 (95% CI, 0.128-0.495) to 0.397 (95% CI, 0.242-0.532). 61 The authors concluded that only a small part of QoL was explained by facial function with use of standard scales. It is thus difficult to accurately determine the relative importance of difference regions of the face in estimating QoL using the standing grading instruments.…”
Section: Qol and Eye Problemsmentioning
confidence: 99%
“…First, we only considered outpatient PFP cases, because NRHIP did not provide information on no-visits and inpatient cases. Due to the impact on appearance and life ( 28 , 29 ), even mild cases usually need to seek medical advice in time. However, hospitalization is generally not required.…”
Section: Discussionmentioning
confidence: 99%